The Formation of the Definite Article in the Nordic Languages - Skrzypek, Dominika (Lingua Posnaniensis, 2010)
The defi nite article in Modern Nordic languages is a suffi x, etymologically related to a demonstrative. The form is not attested in the oldest linguistic sources, the runic inscriptions, but appears fi rst in Icelandic sagas and Swedish and Danish legal codices from 13th century onwards. In these texts it does not appear with the same regularity as in modern languages. Despite numerous attempts to reconstruct the formation of the defi nite article in the Nordic languages, a number of questions remain either controversial or unanswered. The contention issues are the exact etymology of the article and the date of its formation. The demonstrative from which the article grammaticalizes appears in Old Icelandic in two forms: inn or hinn, in Old Swedish as hinn only. However, only inn appears as a clitic. It is argued here that the etymology of inn and hinn may provide an argument in favour of an early formation of the article.